Koncepcija modernizacii processa profesional'noj podgotovki specialistov po fiziceskoj kul'ture i sportu (avtorskij proekt) - Lubyseva, L. I.; Magin, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The authors represent their understanding of the contemporary problems of sport specialists' training in the context of the pedagogical contents of the physical and sports technologies, modernization.